2019
DOI: 10.1039/c8dt03263g
|View full text |Cite
|
Sign up to set email alerts
|

[Ge(TenBu)4] – a single source precursor for the chemical vapour deposition of germanium telluride thin films

Abstract: Reaction of activated germanium with nBu2Te2 in THF solution was shown to be more effective for the preparation of the germanium(iv) tellurolate compound, [Ge(TenBu)4], than reaction of GeCl4 with LiTenBu in THF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The organometallic tin(IV) compound, [ n Bu 3 Sn(Te n Bu)], was selected as a potentially viable single source precursor for the deposition of SnTe thin films since the n-butyl substituents on both the tin and tellurium provide a clean and low energy decomposition pathway via β-hydride elimination, the 1 : 1 Sn : Te ratio in the precursor should aid deposition of the targeted binary phase and avoid incorporation of excess Te, while the volatility of the precursor (oil) was anticipated to be wellsuited to a low pressure CVD procedure. 33 Previous work has shown that film thin deposition from CVD precursors containing n-butyl and other alkyl substituents containing β-hydrogen atoms can often involve β-hydride elimination 34 of alkene and reductive elimination of hydrogen gas or alkane. Moreover, we have shown that n Bu groups can also enhance the prospects of highly area selective deposition of metal chalcogenides onto patterned substrates.…”
Section: Synthesis and Characterisation Of The [ N Bu 3 Sn(te N Bu)] Precursormentioning
confidence: 99%
“…The organometallic tin(IV) compound, [ n Bu 3 Sn(Te n Bu)], was selected as a potentially viable single source precursor for the deposition of SnTe thin films since the n-butyl substituents on both the tin and tellurium provide a clean and low energy decomposition pathway via β-hydride elimination, the 1 : 1 Sn : Te ratio in the precursor should aid deposition of the targeted binary phase and avoid incorporation of excess Te, while the volatility of the precursor (oil) was anticipated to be wellsuited to a low pressure CVD procedure. 33 Previous work has shown that film thin deposition from CVD precursors containing n-butyl and other alkyl substituents containing β-hydrogen atoms can often involve β-hydride elimination 34 of alkene and reductive elimination of hydrogen gas or alkane. Moreover, we have shown that n Bu groups can also enhance the prospects of highly area selective deposition of metal chalcogenides onto patterned substrates.…”
Section: Synthesis and Characterisation Of The [ N Bu 3 Sn(te N Bu)] Precursormentioning
confidence: 99%
“…These precursors include (R 2 GeTe) 3 , where R is Et or Bu, as described by Gupta et al for the thermal decomposition synthesis of GeTe nanoparticles; some often quite elaborate species, including [Ge­{N­(Me 2 SiCH 2 CH 2 Me 2 Si)} 2 i Pr­(Te i Pr)] used in the metal–organic CVD of GeTe thin films by Chen et al. ; [Ge­(Me 2 NCH 2 CMe 2 O) 2 S] and [Ge­(Me 2 NCH 2 CMe 2 S) 2 E] (where E is Se or Te) described for the thermal decomposition synthesis of GeE by Kim et al; [Ge­(S 2 COR′) 4 ] (R′ = Et or i Pr) and [ n Bu 2 Ge­(S 2 CO i Pr) 2 ] described by Shah et al for thermolysis to make GeS; and the use of [Ge­(Te n Bu) 4 ] in LPCVD of GeTe described in our previous work . These precursors are unsuitable for a large number of deposition techniques due to their high molecular weights and low volatilities, as well as poorly defined thermal decomposition pathways, or, in the case of [Ge­(Te n Bu) 4 ], the unbalanced stoichiometry, which leads to some contamination by excess tellurium.…”
Section: Introductionmentioning
confidence: 99%
“…These precursors include (R 2 GeTe) 3 , where R is Et or Bu, as described by Gupta et 34 and the use of [Ge(Te n Bu) 4 ] in LPCVD of GeTe described in our previous work. 35 These precursors are unsuitable for a large number of deposition techniques due to their high molecular weights and low volatilities, as well as poorly defined thermal decomposition pathways, or, in the case of [Ge(Te n Bu) 4 ], the unbalanced stoichiometry, which leads to some contamination by excess tellurium.…”
Section: Introductionmentioning
confidence: 99%